On integration with respect to a DT-measure - Svistula, Marina (Positivity : an international journal devoted to the theory and applications of positivity in analysis, 2016)
DT -measures generalize the topological measures of Aarnes. We continue to study an integral of a real-valued continuous function on compact Hausdorff space with respect to a DT -measure and investigate the following: multiplicativity of this integral, w ∗ -topology on the family of DT -measures and density of various subfamilies of this space, and also integral as a set function.